PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN BANTUAN LEMBAR KERJA SISWA UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI SISTEM GERAK KELAS XI IPS SMAN 3 RAMBAH - Siti Dualom (STKIP ROKANIA, 2021)
The purpose of this study was to explain the process of increasing the activity and learning outcomes of students' biology on the motion system material in class XI IPS at SMA Negeri 3 Rambah, Rokan Hulu Regency with Problem Based Learning. This type of research is classroom action research (CAR). The subjects of this study were students of class XI IPS SMA Negeri 3 Rambah. This study consisted of two cycles, each cycle consisting of planning, implementation, observation and reflection. The research instrument was in the form of student activity observation sheets, and learning outcomes test sheets. The data were analyzed with descriptive statistics to see the increase in student activity and learning outcomes. The results showed that problem-based learning can increase student activities which include paying attention to the explanation of the material presented by the teacher, collaborative activities in groups, making presentations, asking questions and answering questions. The increase in student activity achieved very well at the point of paying attention to the explanation of the material presented by the teacher, cooperative activities in groups, and presentation activities. While the students' learning completeness in the first cycle was 70, in the second cycle, it rose to 80%. The conclusion of this study is that problem-based learning can increase students' activity and learning outcomes in biology on the motion system material in class XI IPS SMA Negeri 3 Rambah.